2015
DOI: 10.1002/tal.1258
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of sliding isolators with variable curvature in near‐fault ground motions

Abstract: Recent studies have revealed that a sliding isolator with variable curvature (SIVC) can mitigate the resonance phenomenon likely to occur in seismic response of a conventional friction pendulum system (FPS) isolator due to its constant isolation frequency. The present study simulates four SIVC isolators and an FPS to find the optimum range of initial isolation period and coefficient of friction and employ them in comparing the effectiveness of SIVC in different peak ground acceleration (PGA) scales of near-fau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…They concluded that such large isolator displacements can be controlled by added viscous fluid dampers. Shaikhzadeh and Karamoddin reported that in a strong near‐fault earthquake, polynomial friction pendulum isolator and variable curvature friction pendulum system or conical friction pendulum isolator and variable frequency pendulum isolator could respectively be chosen based on whether reduction of base displacement or superstructure acceleration is the main concern of the structural designer. The undeniable need to control excessively large unfavorable displacements across the isolation layer was highlighted by Becker and Ezazi while confirming that base isolation was indeed successful in decreasing the accelerations transmitted to a structure.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that such large isolator displacements can be controlled by added viscous fluid dampers. Shaikhzadeh and Karamoddin reported that in a strong near‐fault earthquake, polynomial friction pendulum isolator and variable curvature friction pendulum system or conical friction pendulum isolator and variable frequency pendulum isolator could respectively be chosen based on whether reduction of base displacement or superstructure acceleration is the main concern of the structural designer. The undeniable need to control excessively large unfavorable displacements across the isolation layer was highlighted by Becker and Ezazi while confirming that base isolation was indeed successful in decreasing the accelerations transmitted to a structure.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 16 presents the hysteretic curves of the horizontal force and displacement under different loading frequencies and contact pressures. It can be seen that the hysteretic curves of the horizontal force and displacement are regular, symmetrical, stable, and full, and remarkably reflect the excellent behavior of energy dissipation of the VCFPB (Sharma and Jangid, 2012).…”
Section: Friction Coefficient At the Equilibrium Positionmentioning
confidence: 78%
“…Hong and Hur [18] published a study on systems with the addition of concave and springs to solve convergence problems. Shaikhzadeh presented a numerical simulation and a comparison of the effects of four sliding isolators with variable curvature insulators [19]. Research on RIS using spherical balls instead of cylindrical rollers has also been conducted and applied to light loads [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%